Baroque aesthetics in the works of L. de Gongora and E. Szklyarskiy (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article discusses the phenomenon of Baroque, the features of art style and baroque world-view. It is researched the various stylistic tendencies, the contrast of Spanish Baroque, in which two trends develop and face each other: cultism (culteranizm) and conceptism. The «dark style» of L. de Gongora, which evolves in the poet’s creativity and has its extension in literature and culture of the XXI century, is interpreted. It is analyzed the tragic confrontation of the world and human-being, hidden in the poetry of E. Shklyarskiy who was adherent of the «dark style».
Keywords: baroque; cultism; conceptism; dark style; tragic